(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The article identifies current problems related to the introduction of foreign experience in regulating the activities of commercial banks in the Republic of Uzbekistan and develops scientific proposals aimed at solving them.